Collaborative teaching for DPF40043 and FIN242 subjects: a joint learning initiative / Norazimah Mejri - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2024)
On May 14, 2024, and June 21, 2024, Universiti Teknologi MARA (UiTM) Mukah Campus and Politeknik METrO Betong Sarawak collaborated to provide guidance to finance students from both institutions. The collaborative teaching program focuses on two core subjects: DPF40043 (Politeknik) and FIN242 (UiTM). This collaborative teaching allows students to engage with lecturers from different institutions and foster a sense of community. The lecturers involved in this project shared their expertise and knowledge, providing students with a comprehensive understanding of finance concepts. The virtual classroom setting enabled students to participate in discussions and ask questions.